Stressful Life Events: Coping Strategies and their Relationship to Psychological Adjustment during the COVID -19 Pandemic - Murad, Odeh S.; Al-Majali , Ala’a A. (Dirasat: Human and Social Sciences, 2023)
Objectives: The aim of this study is to determine the level of stressful life events during the spread of the COVID-19 virus, as well as the strategies used to deal with these stressful events and the relationship between stressful life events and psychological adjustment. Methods: A cross-sectional web-based observational study. A survey was carried out among Jordanian universities using random sampling. The validity and reliability of the study tools (Psychological Adjustment Scale, Coping Strategies with Stressful Life Events Scale, and Stressful Life Events Scale) were confirmed. 229 participants, with an average age of 36.15 ± 14.05 years were selected to participate in this study. Results: The findings revealed that the overall level of stressful life events was moderate. Political events were ranked first, followed by economic, emotional, health, social, and family events. The findings also indicated that the positive interaction strategy was one of the most widely used approaches to dealing with stressful life events. Most of the correlations between stressful life events and the degree of psychological adjustment were inverse correlations (r = -0.58, p = 0.01). Conclusions: The individual interacts globally using a positive interaction strategy when facing stressful life events to transform it from a source of fear into a source of success.